Assessing Documentation of Analgesic Prescribing in a Medium Secure Forensic Psychiatric Setting - Bethan Bown; Robert Stamatakis (BJPsych Open)
Aims: This service evaluation sought to assess the consistency of documentation in 5 key areas of analgesic prescribing in a medium secure forensic unit in South Wales.